2015
DOI: 10.5507/bp.2013.083
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sympathectomy after anterior and lateral lumbar interbody fusion procedures

Abstract: Aim. The aim of this study was to identify retrospectively, lumbar sympathectomy (SE) using thermography (TG) and to evaluate clinically, the severity of post-sympathectomy (post-SE) dysfunction after anterior and lateral lumbar interbody fusion procedures (ALIF, XLIF). Methods. Twenty eight patients with suspected SE were referred for TG to both legs. They completed our questionnaire on severity of difficulties after SE. We evaluated the ability of physical examinations to reveal the SE in contrast to TG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Lumbar sympathetic dysfunction (SD), carrying multiple potential clinical presentations such as dislocation, dysesthesia, reduced perspiration, increase in skin temperature, and swelling of the lower limb, has been reported in 4% of patients undergoing lateral transpsoas approaches at T12-L5, though this is 15% lower than the rate of injury documented during anterior approaches at the same levels [15]. Additional possible complications include retrograde ejaculation due to injury to the sympathetic plexus (well known in the urology literature), which occurs more often during dissection of the anterior longitudinal ligament in anterior approaches [16].…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar sympathetic dysfunction (SD), carrying multiple potential clinical presentations such as dislocation, dysesthesia, reduced perspiration, increase in skin temperature, and swelling of the lower limb, has been reported in 4% of patients undergoing lateral transpsoas approaches at T12-L5, though this is 15% lower than the rate of injury documented during anterior approaches at the same levels [15]. Additional possible complications include retrograde ejaculation due to injury to the sympathetic plexus (well known in the urology literature), which occurs more often during dissection of the anterior longitudinal ligament in anterior approaches [16].…”
Section: Discussionmentioning
confidence: 99%
“…Inadvertent injury to LSC during anterolateral approach to spinal column is a known complication which may be underdiagnosed [13,18]. Hrabalek et al [14] reported 28 cases of post-anterior or lateral lumbar interbody fusion with post-sympathectomy syndrome. Sixteen cases (57%) can only be diagnosed by skin thermography without any other sign or symptom.…”
Section: Dextroscoliosis Group (Mm)mentioning
confidence: 99%
“…Lumbar sympathetic chain (LSC) usually runs anterolateral to vertebral body and anterior to psoas muscle [9][10][11] which makes it a structure at risk of injury during this approach. Accidental lumbar sympathectomy during anterior and lateral lumbar interbody fusion had been reported and associates with post-sympathectomy neuralgia and decreased quality of life [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…in 2015 retrospectively analyzed the risk of sympathectomy (utilizing thermography) performing anterior lumbar interbody fusion (ALIF) vs. XLIF procedures between the T12–L5 levels [ Table 1 ]. [ 4 ] They found that ALIF correlated with a 15% rate of sympathectomy versus the 4% encountered with XLIF.…”
Section: Excluding New Neurological Deficits Complications Of Minimamentioning
confidence: 99%